Carbon Capture 2021
DOI: 10.5772/intechopen.93870
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell and Seashells Biomaterials Sorbent for Carbon Dioxide Capture

Abstract: This review aims to explore the application of natural and renewable bioceramics such as eggshell and seashells in carbon dioxide (CO 2) capture from power plant flue gas. CO 2 capture, utilisation and storage (CCUS) is considered a means to deliver low carbon energy, decarbonising industries, power plants and facilitates the net removal of CO 2 from the atmosphere. The stages involved include CO 2 capture, transport of the captured CO 2 , utilisation and secure storage of the captured CO 2. This chapter repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In this regard, Jong-Hyeon et al [43] showed that waste shells, particularly oyster shells, can be used for acid gas treatment in gaseous effluents. In similar studies, quail eggs and oyster shells [183], chicken eggshells [184], and oyster shells [185], have been used to adsorb carbon IV oxide from flue gases successfully. The successful removal of CO 2 can be attributed to the presence of CaO in the shells, which tends to adsorb acid gases.…”
Section: Fig 7 Comparison Between Clean Water and Waste Water From Indoor Domestic Cleaning In Port Harcourtmentioning
confidence: 99%
“…In this regard, Jong-Hyeon et al [43] showed that waste shells, particularly oyster shells, can be used for acid gas treatment in gaseous effluents. In similar studies, quail eggs and oyster shells [183], chicken eggshells [184], and oyster shells [185], have been used to adsorb carbon IV oxide from flue gases successfully. The successful removal of CO 2 can be attributed to the presence of CaO in the shells, which tends to adsorb acid gases.…”
Section: Fig 7 Comparison Between Clean Water and Waste Water From Indoor Domestic Cleaning In Port Harcourtmentioning
confidence: 99%
“…3 shows several examples of these biogenesis calcium wastes. This alternative was introduced because natural resources, such as limestone and dolomite, are non-renewable and energy-intensive to exploit; moreover, the mining process is harmful to the environment and landscape [ 74 ]. Eggshells demonstrate a high CO 2 capture capacity, and a conversion of 76.41% after the first cycle which is close to the theoretical CO 2 capture capacity of CaO, i.e.…”
Section: Classification Of Cao-based Sorbentsmentioning
confidence: 99%
“…The AA, CA, and FA exhibited the maximum carbonation conversion with 54.39%, 55%, and 55.5%, respectively, after 20 cycles because acid modifications altered the surface structure, which decreased the sintering effect after multiple cycles. In addition, pre-treatment of quail eggshells using AA exhibited higher carbonation conversion after 19 cycles than untreated quail eggshells [ 74 ]. Thus, acid modification positively affects CO 2 capture capacity and CaO conversion.…”
Section: Improvement Of Sorbentmentioning
confidence: 99%
“…Due to a massive increase in the exploitation and utilisation of natural resources, waste burden and natural resources scarcity have reached a critical point. 3,7 A transition to sustainable economic systems that use resources more efficiently is necessary. As a consequence, the use of waste bones as a renewable resource as a means of waste management is gaining more attention.…”
Section: Ebikapayementioning
confidence: 99%
“…In addition to posing a waste management challenge, improper disposal creates more environmental burdens and may lead to health issues. 2,3 Landlls are usually the only hygienically and ecologically acceptable disposal method for bone waste. Despite being one of the growing economic and environmental challenges facing the globe, waste is also an incredibly valuable resource today.…”
Section: Introductionmentioning
confidence: 99%